Perceived teacher-student relationship and growth mindset as predictors of student engagement in foreign student engagement in foreign language learning: the mediating role of foreign language enjoyment - Li, Haoting (Frontiers in Psychology, 2023)
This study sought to explore the associations among perceived teacher-student relationship, growth mindset, student engagement, and foreign language enjoyment (FLE) among Chinese English learners. A total number of 413 Chinese EFL learners completed self-report measures of perceived teacher-student relationship, growth mindset, student engagement, and FLE. Confirmatory factor analysis was utilized to check the validity of the scales, and structural equation modeling was used to test the hypothesized model. The partial mediation model was found to be the best fitting model. The results indicated that perceived student-teacher relationship directly affected student engagement. FLE directly affected student engagement, and growth mindset affected student engagement indirectly via the mediation of FLE. The findings suggest that enhancing positive teacher-student relationships and fostering a growth mindset can enhance FLE and ultimately lead to higher levels of student engagement.